The Challenges of Implementing Instagram as Platform in Writing Caption of Digital Marketing - Setia Rini, Ayu; Ulya, Inayatul (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
Expressing ideas in writing caption of promoting products was not easy for students, therefore the researchers tried to optimize the use of social media especially Instagram to establish students’ interest in writing. This research was focused on investigating the strengths and weaknesses of implementing Instagram in writing promotional caption. A descriptive qualitative method was applied in doing the investigation. 31 students of Vocational High School were participated as the subject of this research. To achieve the objective of the study, three instruments were used, they were test, questionnaire, and interview. The test was writing caption through Instagram. The questionnaire was distributed online, meanwhile, the interview was done face to face. Next, the data were analysed and described using qualitative methods. Research findings showed that Instagram contributed positive things to doing writing projects. By using Instagram, students’ writing could be reached by the readers everywhere. Since the material was caption, the students could develop their writing skill of promoting something through Instagram. However, there were found the problems in writing caption using Instagram. It was found that 11 students confused in determining the caption model and did not have any idea about the product to be promoted. In addition, the problem in finding the topic and developing the sentences to be an attractive promotional caption was faced by 16 students. In conclusion, Instagram could be used as a platform to post students’ writing projects, however, the students need to enrich the ideas in writing